The Correlation Between Plankton Abundance And Water Quality in Donan River - Nuraina Andriyani; Arif Mahdiana; Endang Hilmi; Samuel Kristian (Journal Omni-Akuatika, 2020)
Planktons  have ability to live in aquatic ecosystem, including rivers ecosystem, estuary ecosystem, lake ecosystem and ocean ecosystem. The plankton abundance is estimated by correlation with water quality both of salinity, pH, temperature and others. This research aimed to analysis plankton abundance and to analysis correlation between plankton abundance and water quality. This research was conducted in Donan River using random sampling in 10 stations. The plankton are collected  using plankton net no 25 and Lackey Drop Mikrotranset Counting (plankton analysis) and APHA (2005) to analysis water quality. The results showed that the plankton abundance ranged between 524 – 6,406 ind L-1 and best correlation with water salinity had index 0.975. Keywords: plankton abundance, water quality, Donan river, water salinity, correlation